NEUROLOGICAL MANIFESTATIONS OF FABRY DISEASE IN CHILDREN AND ADOLESCENTS - A. S. Kotov; K. V. Firsov (Русский журнал детской неврологии, 2017)
Fabry disease (Anderson–Fabry disease) is an X-linked recessive lysosomal storage disorder resulting from deficient activity of lysosomal hydrolase, alpha-galactosidase A, which leads to progressive accumulation of globotriaosylceramide (Gb3) in various cells (predominantly endothelial and vascular smooth muscle cells) with clinical manifestations affecting major organs including the central nervous system. Clinical onset of Fabry disease usually occurs in childhood, but many patients are diagnosed in adulthood. Early recognition of symptoms, enzyme activity levels, concentration of Gb3 in the blood, urine and skin bioptates, as well as genetic testing (GLA gene) enable establishment of early diagnosis and therapeutic intervention with enzyme replacement therapy. Early therapy may prevent complications of the disease.